Escapology: Transcending Boundaries of Flat Patternmaking and Design Practice - West, Stephanie (Auckland University of Technology, 2016)
This practice-based project explores creative three-dimensional design and patternmaking processes applied to minimal cut and sew garments through an investigation between cloth and body. The question guiding the research was ?Can a different approach to garment shape development, which relates to past practice, be translated and refined to relate to mass production practices?? An answer to the research question was formed by re-instating the designer-maker at the centre of the development process in order to reconnect the cloth with the body, as well as the cloth with the making practice. This resulted in a system of patternmaking, which is referred to as ?The Cube Method?. This is a method of draping geometric shapes guided by cloth movement through and around the bodily form, in order to explore negative space, silhouette and shape. The final stages of the research involved the translation of the three-dimensional designs into a commercial platform for replication through the use of a computer-aided pattern drafting system. This stage of the research revealed reproducible pattern and garment shapes suitable for sustainable mass production, while also protecting the intellectual property of the design.
Keywords: Fashion design; Pattern drafting; Zero waste; Minimal; Cube method; Action research; Cutting; Garment creation; Two-dimensional; Three-dimensional; Sustainability; CAD; Designer-maker; Fashion Industry